2020
DOI: 10.1039/d0py00082e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bonded supramolecular micelle-mediated drug delivery enhances the efficacy and safety of cancer chemotherapy

Abstract: Multiple hydrogen-bonded supramolecular polymers tend to form stable spherical micelles with oppositely charged anticancer drugs in biological environments, which improves cellular drug uptake and more effectively induces apoptosis in cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Targeted nano-drug delivery systems with small sizes (10 to 100 nm) enhance permeation through the newborn blood vessels of tumor tissues with slower clearance due to the lack of lymph 12 . These drug nanocarriers including micelles 13,14 , polymersomes 15 , liposomes 16 , dendrimers 17 , carbon nanotubes 18 , magnetic nanoparticles 19 and silica nanoparticles 20,21 are of high importance because of their higher permeability, detection of target cells, accumulation at cancer sites, less side effects, and more efficient treatment 4,5,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Targeted nano-drug delivery systems with small sizes (10 to 100 nm) enhance permeation through the newborn blood vessels of tumor tissues with slower clearance due to the lack of lymph 12 . These drug nanocarriers including micelles 13,14 , polymersomes 15 , liposomes 16 , dendrimers 17 , carbon nanotubes 18 , magnetic nanoparticles 19 and silica nanoparticles 20,21 are of high importance because of their higher permeability, detection of target cells, accumulation at cancer sites, less side effects, and more efficient treatment 4,5,22 .…”
Section: Introductionmentioning
confidence: 99%
“…First, propargyl-ended difunctional PEG [number-average molecular weight ( M n ), 3000–4000 g/mol] is reacted with azide-functionalized aminopyridinyl amide (DAP) via an azide–alkyne cycloaddition reaction. High-quality DAP-end terminated difunctional PEG (BDAP-PEG) is obtained after purification and dialysis. Subsequently, BDAP-PEG is reacted with uracil via a high-yielding Michael addition reaction to generate BU-DPy-PEG (yield = 90%).…”
Section: Resultsmentioning
confidence: 92%
“…BDAP-PEG was synthesized via a previously described one-step synthetic route . BDAP-PEG (5.00 g, 1.43 mmol) and pyridine (0.24 g, 3.00 mmol) were dissolved in anhydrous tetrahydrofuran (THF, 50 mL) and cooled in an ice-salt bath.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have demonstrated that the drug loading system based on hydrogen bonds not only had high drug loading capacity and excellent stability but also could intelligently release loaded drugs due to the pH responsiveness of hydrogen bonds. 14–16…”
Section: Introductionmentioning
confidence: 99%